Billy Stuart and the Zintrepids - Bergeron, Alain M., 1957- (Bergeron, Alain M., 1957- Billy Stuart., 2018)
"In this illustrated novel for middle-grade readers, Billy Stuart and his loyal Scout group get lost on a hike and inadvertently travel through time."--